Changes in participation for young women after breast cancer diagnosis and treatment: a qualitative study - Amy Roder McArthur; Susan Magasi; Tamara Hamlish; Cassandra A. Winters; Joy Hammel (BMC Women's Health)
Abstract Background Though there is increasing attention to the experiences of young breast cancer survivors, there is a need to further examine participation changes for this population after active treatment. This study aimed to examine how person-environment interactions mediate young breast cancer survivors’ participation in life, focusing on features of disability within breast cancer survivorship. Methods This qualitative study utilized a series of two semi-structured interviews to explore the experiences of nine women diagnosed with early-stage breast cancer at or below the age of forty-five. Interpretative phenomenological analysis was used to analyze interviews. Results Three cross-case themes were identified: (1) Nothing untouched: changes in self (2), Cancer is “not over”: the influences of social environment on survivorship, and (3) Gaps in services and supports: systems level influences on participation. Conclusions Participants’ participation changes were shaped by environmental factors, such as the complexity of healthcare system navigation. Participants pointed to a need to connect young survivors with services and supports to improve opportunities for participation in daily life following breast cancer diagnosis and treatment. This aligns with conceptualizations of disability that identify the environment as a major driver of restricted participation for disabled people. Late effects of breast cancer impact participation and should be routinely addressed as part of cancer and survivorship care. Acknowledging disability as part of breast cancer survivorship can encourage breast cancer survivors to discuss their experiences openly and to ensure they receive the supports needed to participate fully in life.